Fire history in southern Patagonia: human and climate influences on fire activity in Nothofagus pumilio forests - Mundo, Ignacio Alberto (2017)
Fire is a major disturbance affecting forests worldwide with significant economic, social, and ecological impacts. The southernmost forests on Earth extend continuously along the Andes from mid- to subantarctic latitudes in South America. In this region, warming and drying trends since the mid-20th century have been linked to a positive trend in the Southern Annual Mode (SAM), the leading mode of extratropical climate variability in the Southern Hemisphere. Due to the scarcity of documentary fire records and the lack of tree-ring fire histories, little is known about how wildfire activity responds to shifts in the westerly circulation pattern and associated climatic variability in the Andean region south of ~44° S. For the first time, we applied dendrochronological techniques to reconstruct fire history from the angiosperm Nothofagus pumilio at 16 sites distributed from ~44° to 50° S to determine relationships between fire occurrence and the two primary drivers of wildfire activity: climate variability and human activities. Partial cross-sections with fire scars were collected from 363 trees in Argentina and Chile. Chronologies of annually resolved fire-scar dates start in 1791 and show a pattern of higher fire frequency during the 20th century, concurrent with the human occupation and colonization processes in southern Patagonia. Years of widespread fire occurring synchronously in two or more disjunct sites are associated with broad-scale climatic anomalies. Intense droughts inferred from extreme departures in temperature, precipitation, and the Standardized Precipitation-Evapotranspiration Index (SPEI) during the growing seasons of 1944 and 1962 are consistent with the two most severe fires at northern sites. Extended droughts, reflected by the association of fire occurrence with six-month cumulative precipitation and SPEI, create conditions for widespread fires at the southern sites (south of ~46° S). Regional fires were concurrent with significant positive departures of SAM during the austral spring?summer. This tree-ring fire record reveals the influences of both climate variability and human activities on fire in the N. pumilio forests across the Andes, and also establishes the feasibility of using this tree species as a natural archive of fire history.